Efektivitas Penerapan Metode Game-Based Learning untuk Meningkatkan Minat Belajar pada Mata Pelajaran al-Qur’an Hadist Kelas VI DI MIS Sidorejo Tirto Pekalongan - Hidayah, Nur; Diah Pramesti, Santika Lya (Indonesian Journal of Islamic Elementary Education, 2023)
The purpose of this study was to determine the effectiveness of applying the game-based learning method to increase interest in learning in class VI Al-Qur'an Hadith at MIS Sidorejo Tirto Pekalongan. The formulation of the problem in this study is as follows: 1) How is the interest in learning in the Al-Qur'an Hadith class VI subject at MIS Sidorejo Tirto Pekalongan before implementing the game-based learning method? 2) How is the implementation of the game-based learning method in class VI Al-Qur'an Hadithat MIS Sidorejo Tirto Pekalongan? 3) What is the effectiveness of applying the game-based learning method to increase interest in learning in class VI Al-Qur'an Hadith at MIS Sidorejo Tirto Pekalongan. This research method is a quantitative type of experiment with research subjects of class VI students at MIS Sidorejo for the 2021–2022 academic year. The total population is 54 students from two classes. Then the researcher used simple random sampling to determine the experimental class and the control class. The result is that the experimental class is VI-A with 27 students, and the control class is VI-B with 27 students. Data was collected using a questionnaire technique and analyzed using an independent sample t-test analysis technique.The results of this study indicate: 1) the application of the game-based learning method shows a result of 62% in the range of 50%–74%, which is included in the good category. 2) Students' interest in learning Al-Qur'an Hadith subjects in the experimental class showed results of 41.7% in the range of 25%–49%, which was included in the pretty good category, while in the control class, results of 50% in the range of 50%–74% were included in the good category. 3) The effectiveness of applying the game-based learning method using an independent sample t-test in SPPS version 26 shows sig. (2-tailed) results of 0.0080.05. This means that Ho is rejected and Ha is accepted.